A concise guide to education studies - Hindmarch, Duncan; Hall, Fiona; Machin, Lynn; Murray, Sandra (Education studies, 2017)
Explores key contemporary issues in education, featuring the latest theoretical perspectives and policies, aimed at supporting the professional development and understanding of those working or intending to work in the education sector.